The Wages policy after Enactment of Government Regulation Number 78 year 2015 on Wages in Indonesia - Lalu Adhi Adha (Unram Law Review, 2017)
The emerge of pros and cons as always on the issue of minimum wages was a fact that indicates that wage issues are still a controversy and never done. The other hand, it can also be an indicator of the increasing awareness of workers to claim their rights. However, in case more examined closely the emerge of them are from the unaccommodated policies that are made. The determination policy of minimum wage has only understood an attempt to adjust to macroeconomic changes, but has never been seen in the context of real income development for workers. The exposure has been written in this research, in effect to provide the alternative solutions for the realization of the accommodative wage policy. In this context, the government was required to neutral stand and accommodative functioning. In the end, the wage policy formulation analysis described and the analysis in this, to expected and create more comprehensive. Thus, the relationship between economic actors in industrial workers, employers and governments can work synergistically for better economic order.